Eu só queria saber por que o óvulo tem que ser da ovelha? Situando o processo de construção de significados na sala de aula de Biologia - Machado, Ligia Cristina Ferreira (2009)
This thesis in the field of Science, Society and Education seeks to investigate the epistemic practices which take place in the Biology classroom in order to characterize it as a community of practice. This study is based theoretically in two main points: the first deals with the notion of learning and situated learning from a socio-cultural point of view (WERTSCH; DEL RIO; ALVAREZ, 1998; WERTSCH, 1998 and 1999; LAVE; WENGER, 1995 and ENGLE; CONANT, 2002) and the second joining works in Sociology of Science (LATOUR, 2000 and KNORR-CETINA, 1981 and 1992) and works produced by the research in Science Education which deals with laboratory analyses and Science classrooms, respectively, eliciting, particularly, the process of construction of scientific meaning. From this theoretical matrix, a teaching unit, Unveiling the secrets of life: reproduction in the molecular level, was developed and video-recorded during two months in a first grade Telecomunicações of Ensino Médio at CEFET, Nova Iguaçu, Rio de Janeiro. This group also answered a questionnaire applied before the beginning of the teaching unit to know the students conceptions about the subject. The analysis of the recordings was based on the methodology proposed by MORTMER and SCOTT (2002) and MORTIMER et al (2007) which permitted the selection of interactional sequences where epistemic practices emerged related to the process of construction/production of biological meaning when students interrelated different levels of meaning (structural procedural and representational) which display a certain biological form of thinking, speaking and interacting with the world. This aspects places the Biology classroom as a time-space of epistemic and social practices characterizing it as a community of practice owing to the fact that the students engate in processes of in-tense negotiation of meanings which are re-elaborated and re-described in the relationship with other objects and processes from a biological perspective.